Toxic effect of human polymorphonuclear leukocytes on Chlamydia trachomatis. - Yong, E C (1982)
The effect of human polymorphonuclear leukocytes (PMNs) on Chlamydia trachomatis was studied. Both trachoma (B/TW-5/OT) and lymphogranuloma venereum (L2/434/Bu) biotypes were rapidly inactivated by exposure to human PMNs. A decrease of 3 to 3.5 logs in viable count was observed after 60 min of incubation at a chlamydia-to-PMN ratio of 1:10. Both chlamydial biotypes were also rapidly inactivated by the cell-free myeloperoxidase-H2O2-halide system. A decrease in infectivity titer of 4 to 5 logs for TW-5 and complete inactivation of 434 were seen after 30 min of incubation. The microbicidal effect was prevented by the deletion of each component of the system or by the addition of the peroxidase inhibitors cyanide or azide. PMNs from myeloperoxidase-deficient patients inactivated chlamydiae normally, whereas PMNs from patients with chronic granulomatous disease, although strongly chlamydicidal, were less effective than normal PMNs in the activation of TW-5 (2-log drop in viable organisms versus a 3 to 3.5-log drop). The chlamydicidal activity of PMNs from patients with chronic granulomatous disease and normal PMNs were comparable against the 434 biotype. These studies suggest that the myeloperoxidase system, or indeed oxygen-dependent antimicrobial systems, are not essential for the chlamydicidal activity of PMNs.